Ecological aspects and hunting sustainability of paca (Cuniculus paca) in the Itaya river basin, Peruvian Amazonia - Aquino, Rolando (2009)
This report contains information about sleeping dens, population structure and the impact of hunting of the paca (Cuniculus paca Linnaeus, 1766). It is based in sleeping den observations, transect censuses and hunt- ing records. We found that each sleeping den has one to three orifices for regular access and way out, one to four orifices for circumstantial escape, and an internal cavity for the diurnal sleep. Of the total sleeping dens inspected, 67% where located between 0 and 60 m from water bodies, but some were also found as far as 100 m away. Of the population extracted by hunters, 74% were adults and only 4% were infants. The annual hunting pressure was estimated at 0,4 individuals/ km2 and the population density for the overall area at 6,2 individuals/ km2. Finally, the harvest model suggests that hunting of the paca is sustainable in Alto Itaya river basin.